TINGKAT SERANGAN BAKTERI Aeromonas hydrophila PADA BEBERAPA ORGAN IKAN MAS KOKI (Carasius auratus) DI CV. SERAMBI IKAN CENTER LAMBARO, ACEH BESAR - Henny Dameria Sihite; Suri Purnama Febri; Andika Putriningtias; Eti Tresnowati (Universitas Teuku Umar, 2025)
In Carassius auratus cultivation activities there are many problems that are generally faced by farmers, one of which is disease. This study aims to find out what organs are identified, determine the clinical symptoms in goldfish (Carassius auratus) which are attacked by Aeromonas hydrophila bacteria and determine the prevalence level of Aeromonas hydrophila bacteria in Carassius auratus. Fish samples were taken randomly as many as 14 fish samples with a size of 5-10 cm. The research results showed that 7 goldfish samples were infected with Aeromonas hydrophila bacteria in fish 1 (liver and skin), fish 4 (liver and kidney), fish 5 (kidney and skin), fish 6 (skin), fish 7 (kidney), fish 8 (skin), and fish 10 (liver). The prevalence rate of Aeromonas hydrophila bacteria in goldfish was found to be 50%, which is a significant threat to fish health.Key words: Aeromonas hydrophila, Carassius auratus, biochemical test, prevalence